2021
DOI: 10.1002/ceat.202000300
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant Polymorphism and Nucleation Control of DL‐Methionine Through Antisolvent Crystallization

Abstract: The concomitant polymorphism of the sulfur‐containing essential amino acid DL‐methionine was revealed, and α‐ and β‐polymorphic forms were separated from aqueous solution through antisolvent crystallization with ethanol as antisolvent. The addition of different volume fractions of ethanol into the mother solution reduces the solubility of DL‐methionine in double‐distilled water and in turn proportionately generates a range of supersaturation levels. This induces the nucleation of a stable β‐polymorph at low su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…According to the POM photographs of the crystallized products, at a FA/W ratio of 1:1, platelike particles were obtained, corresponding to the typical crystal habit of Form I (Figure 3a); while needle-like crystals representing Form II are obtained at a FA/W ratio of 2:1 (Figure 3b). 38,39 Previously, Srinivasan et al 40 prepared methionine polymorphs by adding different amounts of ethanol in water, i.e., β crystals were obtained as the volume fraction of ethanol was less than 0.06, while the α crystals were obtained at a high ethanol fraction (>0.1). Thus, it is important to reveal the reason that results in the formation of distinct polymorphs under different solvent/antisolvent ratios.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the POM photographs of the crystallized products, at a FA/W ratio of 1:1, platelike particles were obtained, corresponding to the typical crystal habit of Form I (Figure 3a); while needle-like crystals representing Form II are obtained at a FA/W ratio of 2:1 (Figure 3b). 38,39 Previously, Srinivasan et al 40 prepared methionine polymorphs by adding different amounts of ethanol in water, i.e., β crystals were obtained as the volume fraction of ethanol was less than 0.06, while the α crystals were obtained at a high ethanol fraction (>0.1). Thus, it is important to reveal the reason that results in the formation of distinct polymorphs under different solvent/antisolvent ratios.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, Srinivasan et al prepared methionine polymorphs by adding different amounts of ethanol in water, i.e., β crystals were obtained as the volume fraction of ethanol was less than 0.06, while the α crystals were obtained at a high ethanol fraction (>0.1). Thus, it is important to reveal the reason that results in the formation of distinct polymorphs under different solvent/antisolvent ratios.…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, if the supersaturation ratio was too high, liquid–liquid phase separation would lead to no crystals, as shown in Figure . Suresh et al revealed the effect of supersaturation levels on the polymorphic form of dl -methionine obtained by antisolvent crystallization, during which the supersaturation was proportionately generated by change in the antisolvent concentrations, as shown in Figure . The results indicated that the stable β-polymorph formed at low supersaturation levels, while a mixture of α- and β-polymorphs was detected at intermediate supersaturation levels, and the metastable α-form was obtained at high supersaturation levels .…”
Section: Traditional Methods For Preparation and Regulation Of Drug P...mentioning
confidence: 99%
“…The results indicated that the stable β-polymorph formed at low supersaturation levels, while a mixture of αand β-polymorphs was detected at intermediate supersaturation levels, and the metastable α-form was obtained at high supersaturation levels. 20 Form I and form II of clopidogrel hydrogen sulfate have been widely applied in the cure of thrombotic diseases. Reactive crystallization is one of the most used techniques for the industrial production of form I of clopidogrel hydrogen sulfate.…”
Section: Traditional Methods For Preparation and Regulation Of Drug P...mentioning
confidence: 99%
“…Recent studies have revealed the detailed kinetics of orientated attachment and the importance of desolvation on particle aggregation during crystal nucleation [80,151]. The large barrier of this step results in the rare event of crystal nucleation, which may also produce simultaneous nucleation of two crystal structures (polymorphs) [152][153][154], i.e., concomitant crystallization of polymorphs when the nucleation barrier for two polymorphs were comparable. Furthermore, the absence of structure correspondence and solvent-dependent molecular association indicate multiple aggregates of solutes regulated by their surrounding environment that is formed either in pre-nucleation or in the course of nucleation stages.…”
Section: Aggregation-based Multiple Nucleation Pathwaysmentioning
confidence: 99%